Pairing (CRIA) With Playful Interaction Design : From Teaching to a Tool in Design Education - Heljakka, Katriina (United States, 2026)
Play has the potential to act as a civic method that benefits democracy by operationalizing the core principles of Child Rights Impact Assessment (CRIA) in accessible, inclusive, and future-oriented ways. A tool developed in Finland as the result of a teaching innovation in playful and gameful design exemplifies how humanities students can translate interaction design into a participatory tool for children, advancing child rights in decision-making. Mirrored against the principles of CRIA, the tool presented in this study on design education demonstrates systematic assessment through rule-based play formats, ensures participation by lowering barriers via narrative role-play, and fosters transparency by making collective outcomes visible to all participants. Importantly, the analysis of the teaching innovation presented through a design educator’s perspective situates this work within the framework of the child’s right to play, as recognized in Article 31 of the United Nations Convention on the Rights of the Child (UNCRC, 1989) and clarified in General Comment No. 17.Keywords: Playful democracy, Child Rights Impact Assessment (CRIA), CRIA Tool; Children’s Right to Play, Interaction design in Humanities, Participatory governanceIntroductionThe right of the child to play is a cornerstone of international human rights law. Article 31 of the United Nations Convention on the Rights of the Child (UNCRC, 1989) affirms that every child has the right to “rest and leisure, to engage in play and recreational activities appropriate to the age of the child.” This right has been further clarified in General Comment No. 17 (UNCRC Committee, 2013), which emphasizes that play is a fundamental aspect of children’s wellbeing, learning, and participation in society. As Lester and Russell have argued, play enables children to “make sense of the world and their place in it.” At the same time, Ginsburg underscores its role in strengthening not only individual growth but also relationships and collective engagement. Play must be taken into account when listening to the views of children, and children have the right to express their opinions and influence decisions made in Finland, where the study at hand was undertaken. Despite this recognition, play often remains marginalized in governance processes. Policy frameworks such as “lapsivaikutusten arviointi” (LAVA), Finland’s national model of Child Rights Impact Assessment (CRIA), aim to systematize the consideration of children’s rights in law and policy. CRIA, or LAVA in Finland, refers to the systematic process of analyzing the potential effects of policies, legislation, or administrative decisions on children. In this context, play offers an underexplored but promising pathway. Play can lower barriers to participation, create inclusive and multimodal spaces for expression, and render decision-making processes tangible through narrative and material outcomes. By embedding democratic principles within rule-based structures integrated in playful tools, play enables children to experience participation as a lived practice rather than an abstract right. Moreover, play’s imaginative and future-oriented dimensions provide tools for anticipating the impacts of policies, resonating with LAVA’s emphasis on foresight. A concrete example of this potential is the “Teddy Council”, a playful tool developed in Finland as part of teaching in playful and gameful design. Emerging from this course in interaction design taught to humanities students, this tool uses teddy bear narratives, tokens, and playful voting structures to invite children into collective decision-making. In doing so, it transforms the bureaucratic logic of CRIA into embodied, accessible, and transparent forms of play. From a pedagogical perspective, it also illustrates how design literacy can be cultivated in the humanities to produce innovations that are both playful and policy-relevant.This presentation proposal focuses on how playful interaction design was utilized as part of teaching playful and gameful design to a group of humanities students in Finland, and how a tool for Child Rights Impact Assessment was developed to mirror the principles of LAVA, to provide an accessible, scalable, and transparent tool to meet the needs of the local municipality.The analysis of the teaching innovation that resulted in the creation of the CRIA tool highlighted several contributions of pairing CRIA with playful interaction design, including novelty, relevance, play as a method for participation, the important role of materiality in playful interaction design, inclusivity achieved through multimodality and embodied interaction, and the importance of expertise involved in the teaching dimension.
Keywords: Playful democracy, Child Rights Impact Assessment (CRIA), CRIA Tool, Children's Right to Play, Interaction Design in Humanities
Artificial Intelligence and Social Computing 2025 : Proceedings of the 16th International Conference on Applied Human Factors and Ergonomics and the Affiliated Conferences, Orlando, Florida, USA, 26-30 July 2025